Culture, politics and identity: critical readings on gender in southeast Asia - Santos, Clara (2012)
This article discusses some critical readings of theoretical texts on gender in Southeast Asian countries, where the intersections of past and present, of the global and the local, capitalism, post-colonialism and post-modernism define the guidelines to explore the negotiation and evolution of gender concepts. Gender issues are located not only within structures of symbolic meaning, but also in relation to the historical and political forces that have marked a plurality of post-colonial contexts, where local notions about gender (in)equality and complementarity are constantly evolving. This article claims that the previously silenced narratives of non-Western women must be given a new role and status, in a modern transnational, interdisciplinary cultural grid. Narratives of everyday common life create spaces of empathy, and consequently, projects of action and research will be conducted in order to obtain concrete and useful results. However, many narratives of the everyday practice are actually stories of violence, a type of discourse generated by extreme poverty, substantial inequality and daily contact with terror. In addition, this article also analyses the role played by female characters in the building of the nation’s narrative, both in colonial and post-colonial times, with its enduring stereotypes, dichotomies and metaphors of power.